WEB BASED CONTAINER RENTAL INFORMATION SYSTEM - M Fakhriza; Desy Ramatika (Journal of Information Technology, computer science and Electrical Engineering, 2025)
This web-based container rental information system is designed to enhance efficiency and simplify management in the container rental process. The system addresses common challenges in manual operations, such as data recording, container availability monitoring, and transaction handling between renters and service providers. Developed using the waterfall method, the system follows a structured approach through stages of requirements analysis, system design, implementation, testing, and maintenance. This responsive, web-based system is connected to a database, allowing access from various devices, including computers and smartphones. The main features of the system include container searches based on specific criteria, online booking, rental status tracking, and automated notifications via email or SMS. Additionally, the system includes a dashboard that provides financial reports and rental statistics, assisting management in real-time data analysis. Data security is ensured through user authentication and authorization, allowing only registered users to access certain information.Testing results demonstrate that the system effectively minimizes data entry errors, speeds up the rental process, and simplifies inventory management. The implementation of this web-based container rental system is expected to improve service quality for providers and offer users a more convenient, efficient, and secure rental experience. Through these capabilities, the system supports a more structured rental process that aligns with modern service expectations, benefiting both providers and renters alike.